A Humanistic Overview: Implementation Of Independent Learning For Arabic At Islamic Universities - Winarti, Endah; Fauziah, Fauziah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this study is to describe the implementation of Merdeka Belajar (Independent Learning) of Arabic in universities and analyze the humanistic review of the performance of Merdeka Belajar (Independent Learning) of Arabic in Islamic universities in Indonesia. The research method used is a qualitative approach with the type of multicluster study research by comparing the implementation patterns of Merdeka Belajar (Independent Learning) in Indonesia. Data were collected using interview techniques, observations, and documentation studies on implementing Merdeka Belajar (Independent Learning) in Islamic universities. The data analysis technique used in this study uses data reduction, display, verification, and conclusion. The results of this study show that the implementation of Merdeka Belajar (Independent Learning) of Arabic in Islamic universities is realized in the form of student exchanges, the implementation of internship programs in various agencies that have strengthened the experience of prospective graduates, and the realization of humanistic aspects in the implementation of independent learning of Arabic at Islamic universities in, both from educational-cultural, philosophical, and intellectual aspects.